Pengaruh Pemberian Remisi Terhadap Perubahan Mental dan Sikap Narapidana Pada Rumah Tahanan Kelas IIB Jembrana - Tangkas, I Putu Krisna Putra; Hariyanto, Diah Ratna Sari (Kertha Wicara : Journal Ilmu Hukum; Vol 9 No 12 (2020), 2020)
The purpose of this study is to examine the effect of granting remissions as an aspect of mental change and attitudes of prisoners at Jembrana Class IIB State Detention Center and the process of giving remissions at Class IIB State Detention Centers in Jembrana. The method used in this research is empirical legal research method. The approach used in writing this journal is a factual approach, which means taking an approach by conducting a field study of the process of giving remissions to the behavior of prisoners. The results of the study show that by giving remissions to prisoners, it can motivate inmates to behave positively and participate actively in the coaching process by restoring confidence in themselves, namely that their good behavior is recognized by proposing remission. The process of granting remissions at the Class IB State Detention Center in Jembrana is in accordance with applicable regulations. In this regard, prisoners who should have received remission in accordance with the results of the Correctional Observer Team (TPP) trial are still considered to have their rights, but on the other hand, prisoners who violate the rules and regulations recorded in register F are subject to sanctions without giving remission which is their right.   Keywords: Prisoners, Remission, State Detention Centers